Two Congeneric Shrubs from the Atacama Desert Show Different Physiological Strategies That Improve Water Use Efficiency under a Simulated Heat Wave - Enrique Ostria-Gallardo; Estrella Zúñiga-Contreras; Danny E. Carvajal; Teodoro Coba de La Peña; Ernesto Gianoli; Luisa Bascuñán-Godoy (Plants, 2023)
Desert shrubs are keystone species for plant diversity and ecosystem function. Atriplex clivicola and Atriplex deserticola (Amaranthaceae) are native shrubs from the Atacama Desert that show contrasting altitudinal distribution (A. clivicola: 0–700 m.a.s.l.; A. deserticola: 1500–3000 m.a.s.l.). Both species possess a C4 photosynthetic pathway and Kranz anatomy, traits adaptive to high temperatures. Historical records and projections for the near future show trends in increasing air temperature and frequency of heat wave events in these species’ habitats. Besides sharing a C4 pathway, it is not clear how their leaf-level physiological traits associated with photosynthesis and water relations respond to heat stress. We studied their physiological traits (gas exchange, chlorophyll fluorescence, water status) before and after a simulated heat wave (HW). Both species enhanced their intrinsic water use efficiency after HW but via different mechanisms. A. clivicola, which has a higher LMA than A. deserticola, enhances water saving by closing stomata and maintaining RWC (%) and leaf Ψmd potential at similar values to those measured before HW. After HW, A. deserticola showed an increase of Amax without concurrent changes in gs and a significant reduction of RWC and Ψmd. A. deserticola showed higher values of Chla fluorescence after HW. Thus, under heat stress, A. clivicola maximizes water saving, whilst A. deserticola enhances its photosynthetic performance. These contrasting (eco)physiological strategies are consistent with the adaptation of each species to their local environmental conditions at different altitudes.